Maxilla reconstruction with autogenous bone block grafts: computed tomography evaluation and implant survival in a 5-year retrospective study - Gulinelli, J. L.; Dutra, R. A.; Marão, H. F. [UNESP]; Simeão, S. F.P.; Groli Klein, G. B.; Santos, P. L. (Elsevier, 2017)
This retrospective study was performed to evaluate the bone thickness of the anterior maxillary region after reconstruction with autogenous bone blocks at 6 months and 5 years after surgery using computed tomography (CT) and to determine the implant survival rate. Eleven patients with a horizontal bone deficiency were treated with reconstructive procedures and implant placement. CT measurements were obtained before surgery (T0) and at 6 months (T1) and 5 years (T2) after surgery. The values were analysed statistically (analysis of variance and Tukey's test; P < 0.05). Implant survival was evaluated at follow-up. The mean width of the lower region of the ridge (± standard deviation, in millimetres) was 3.8 ± 1.6 at T0, 7.0 ± 1.6 at T1, and 6.5 ± 1.0 at T2; the mean width of the upper region of the ridge was 5.7 ± 2.3 at T0, 8.3 ± 2.2 at T1, and 7.3 ± 1.6 at T2. The mean total thickness of the ridge was 4.7 mm at T0, 7.6 mm at T1, and 6.9 mm at T2; the average increase in horizontal thickness was 2.9 mm at T1 and 2.2 mm at T2. A statistically significant difference was observed in the mean width of the lower portion at T1 and T2 compared to the width at T0. The implant survival rate was 94.1%. This technique demonstrated high predictability for implant survival, with a reduction in the graft bone during the follow-up period.
Keywords: bone graft; dental implant; maxilla; tomography